PERTANGGUNGJAWABAN PIDANA PEJABAT PUBLIK TERHADAP TINDAK PIDANA KEBOHONGAN PUBLIK DALAM UNDANG-UNDANG NOMOR 14 TAHUN 2008 TENTANG KETERBUKAAN - Taufiq Tri Adi Sunarko, I Nyoman Serikat Putra Jaya, Purwoto (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
Public Information on the other hand leads to a fear of when the information is received by the public is the public information that is false or misleading, and may be referred to the Public Lies. Public Lies can be made by anyone, including the public officials themselves. Public officials who make Public Lies need to get tough sanctions such as criminal sanctions, for acts committed public officials has the emergence of a reason kriminogen other crimes, thus need for the criminal responsibility of they are Public Lies done.